Depression and associated factors in people living with HIV/AIDS in Quindio, Colombia, 2015 - Deisy Viviana Cardona-Duque; Oscar Adolfo Medina Perez; Sandra Milena Herrera Castaño; Paula Andrea Orozco Gómez (Universidad de Ciencias Médicas de La Habana, 2016)
Introduction: Antiretroviral Therapy has been an effective response to HIV infection, however, some psychological variables can interfere with adaptation to treatment and quality of life of patients because this is a chronic disease. Objective: To identify indicators of depression and associated factors in a group of people living with HIV / AIDS in Quindio, Colombia. Material and Methods: A cross-sectional study was performed in a group of 70 adults diagnosed with HIV were receiving antiretroviral treatment in Quindio, Colombia. The information was obtained through questionnaires Beck´s depression and anxiety, the questionnaire MOS social support and a survey on socio-demographic information, family and health aspects. Results: The average age stood at 38,2 years old; (DE 12,6) 64.5% were men, 44,9% were single, 30% scored moderate or severe levels of depression. Having relationship acted as a protective factor of depression: for each patient relationship and moderate or severe levels of depression, there were 6 separated or widowed (P = 0,006; RP = 5,769; IC 95%: 1,349 - 24,674). High or moderate levels of anxiety were associated with depression (P = 0,004; RP = 2,750; IC 95% 1,391 - 5,436). Conclusions: Depression can affect often people living with HIV and high levels of anxiety associated with it. Having a relationship could favor the mood in these patients, probably because it is a source of social support.   Keywords: Antiretroviral therapy, highly active; anxiety; depression; emotional adjustment; HIV; social support.